Listening to NFC at higher harmonic frequencies - Kryzhanovskyi, V.G.; Serhiienko, S.P.; Chernov, D.V.; Kryzhanovsky, V.V. (Radiotekhnika, 2021)
The widespread use of the NFC technology (Near Field Communication) arouses interest to various security aspects. There are known examples of information exchange with card at a distance greater than standard 5-10 cm. It is also interesting to use signals of higher harmonics, which potentially may be radiated in the form of electromagnetic waves, rather than exists as a magnetic field of scattering. In this work, the radiation of third harmonic by card of standard ISO 14443-3А with the fundamental frequency 13.56 MHZ for various excitation modes using the RFID-RC522 reader, smartphone Sony Xperia Z5 Premium, and continuous 10% amplitude modulated 13.56 MHz signal from generator with the subcarrier of imitated smart card response 847.5 kHz was investigated. The card response at third harmonic was simulated in circuit analysis software. Both simulation and experiment proved, that the third harmonic with its side frequencies 40,68 ± 0,8475 MHz have the highest level after the fundamental. To receive the third harmonic signal, the resonant loop antenna in the form of ring vibrator loaded on capacitor was used. This allows the sizes of the received system to be reduced, but the problem of complex field structure in the near-field zone remains. Due to narrow bandwidth of the receiver antenna, the registration of card response signal was complicated. The experiments with three methods of signal generation proved, that third-harmonic signal is registered at the distance more than 1.5m, which may pose a threat for contactless smart-cards transactions security. At the same time, the influence of high level of noise at such a distance may cause difficulties to decode the short-duration signals, which requires further study.